More Choices Than You Might Think: A Review of Organization Theory Textbooks - Mentzer, Marc S. (Academy of Management Review, 1987)
The article presents reviews of many textbooks, including “Organizations: Theory and Analysis,” by A.G. Bedeian, “Organization Theory: Integrating Structure and Behavior,” by G. Dessler, and “Organizational Theory and Design: A Strategic Approach for Management,” by E.A Gerloff.